DIGITAL LITERACY ON THE PEDAGOGICAL COMPETENCE OF ELEMENTARY SCHOOL TEACHERS - Sari Mahfiroh; Nurkolis; Rosalina Br Ginting (Universitas Islam Negeri Mataram, 2026)
This study aims to analyze the effect of digital literacy on the pedagogical competence of elementary school teachers in Sayung District, Demak Regency. The research is motivated by the gap between the demands for digital innovation in the curriculum and the relatively low level of teachers’ pedagogical quality, particularly in areas facing geographical challenges such as tidal flooding (rob). This study employed a quantitative approach with an ex post facto research design. Data were collected from 177 elementary school teachers as respondents through questionnaires measuring digital literacy and pedagogical competence variables. Data analysis was conducted using descriptive statistics and linearity tests through SPSS software. The results show that the mean score of digital literacy was 130.33, while the mean score of pedagogical competence was 204.12. The linearity test yielded an F value of 394.391 with a significance level of 0.000, indicating a very strong and positive linear relationship between the variables. In conclusion, digital literacy serves as a fundamental catalyst that significantly enhances teachers’ pedagogical professionalism. These findings emphasize that educational transformation relies more on the depth of teachers’ digital literacy as an instrument of resilience than merely on the provision of physical infrastructure